He putiputi, he taonga, he rangatira : the factors motivating young Maori women to achieve success : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Palmerston North, New Zealand - Bosmann-Watene, Gail (Massey University, 2009)
This thesis is a study of the factors that motivate young Māori women to achieve success. Six Māori women aged between fifteen and twenty six years were interviewed for the purpose of identifying what motivates them and to explore their perceptions of motivation, achievement and success. All of the young women have achieved across many facets within their lives but were chosen for this study because of their high achievements in sport, education and business. Jodi Te Huna, Kayla Sharland, Hinurewa Poutu, Amanda Gimblett, Christall Raukawa Lowe and Te Kaihou Ngarotata are the voices within this research. Their experiences, perceptions and ideas about motivation and achieving success are presented as case studies. Informed by a Māori worldview, Maāori research methodologies are blended together and are the foundation of this research. Grounded theory and Feminist approaches to research were also utilised alongside Māori methodologies which provide the researcher with the path to navigate the research process. The six Māori women who participated in this study are the heart of this research and through their voices they offer knowledge enabling the researcher to walk the path. The research found that a supportive environment is essential in motivating people. Whānau were identified as the primary external motivating factor which reflected a wide range of support systems. Using social learning theories to explain the internal intricacies of why we behave in a motivated way, the study found that the participants within this research were driven by intrinsic factors and instilled values which influenced them to behave in a motivated way. Self efficacy was also a factor motivating them to achieve their successes. The study also found a clear connection between external and internal motivating factors. Specifically, external motivating factors cultivate internal motivating factors. This study has been undertaken by a Māori woman, for and on behalf of Māori women. It contributes to the growing voice that Māori women are carving out in research and provides evidence that Māori women do achieve, can achieve and will continue to achieve.
Keywords: Women Achievement motivation; Maori Women Attitudes; Maori Women Interviews; Case studies